Diseño de identidad corporativa de las carreras profesionales de la Universidad Técnica De Cotopaxi mediante la elaboración de un manual corporativo para cada unidad académica, conservando la imagen institucional para difundirla en la colectividad, durante el periodo 2014-2015 - Betancourt Guachamin, Johanna de los Angeles (2014)
The present research conceived “Cotopaxi Technical University careers’ corporate identity design through a development manual for each academic unit, for keeping the institutional image in order to spread it. The same will be able to meet the need of identification of an effective visual way, this will let that the races can be differentiated. For this direct observation and surveys was applied which allowed the information collection to determine the main characteristics and elements used for logos illustration of each race of the institution. The project was carried out positively at Cotopaxi Technical University. It has achieved wide acceptance in students and authorities. The investigation offers a framework, theoretical framework and methodology. The proposed design is intended proper use of the image, implementation manuals are made with the main reason why students and authorities identified with the institution and this in turn can be organized properly. During project development issues of great importance are cited in Graphic Design such as typography, color, correct and incorrect uses of the logo, minimum reduction, stationery, promotional, and digital application. It is important to note that the project objectives were met in full.